The Authority of Notaries and Land Deed Officials (PPAT) in Controlling the Conversion of Sustainable Food Agricultural Land (LP2B) during the Transfer of Land Rights - Rita Devi Permatasari; Rachmad Safa’at; Herlindah Herlindah (Program Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam Sultan Agung, 2026)
This study aims to analyze the authority of Notaries and Land Deed Officials (PPAT) in controlling land-use conversion of Sustainable Food Agricultural Land (LP2B) during the transfer of land rights and to examine the juridical implications arising from such authority. The research is grounded on the existence of normative ambiguity and the lack of integration between notarial authority and spatial planning control systems, which creates legal gaps enabling formal yet unlawful land conversion. This research employs a normative juridical method with statutory, conceptual, and case approaches. The findings indicate that the authority of Notaries and PPAT remains general in nature and does not explicitly impose obligations to verify LP2B status, resulting in the suboptimal preventive function as gatekeepers. The juridical implications include potential invalidity of authentic deeds, administrative, civil, and criminal liabilities, as well as legal uncertainty and weakened spatial control effectiveness. Therefore, a comprehensive regulatory reconstruction is required to strengthen the preventive role of Notaries and PPAT in controlling land conversion in order to support national food sovereignty.